1988
DOI: 10.1161/01.str.19.8.963
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of CO2-induced cerebral vasomotor response in normal individuals and patients with internal carotid artery occlusions.

Abstract: To evaluate the CO 2 -induced vasomotor reactivity of the cerebral vasculature, relative changes of blood flow velocity within the middle cerebral artery were measured by transcranial Doppler ultrasonography during normocapnia and various degrees of hypercapnia and hypocapnia. We studied 40 normal individuals and 40 patients with unilateral and 15 patients with bilateral internal carotid artery occlusions. When blood flow velocity changes as percent of normocapnic values were plotted against end-tidal CO 2 vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
331
1
14

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(364 citation statements)
references
References 41 publications
18
331
1
14
Order By: Relevance
“…This negative reactivity may indicate a steal effect, a paradoxical response that has been observed in some patients with severe carotid artery disease. 18 The normal velocity response to hypercapnia in healthy subjects without occlusive disease (2.9-3.5%/mm Hg change in PecxV 9 -20 ) appears to be constant over the physiologic range of 20-60 mm Hg. Among patients with unilateral carotid artery occlusions, Ringelstein et al 18 have shown that vasomotor reactivity measured by TCD is severely reduced, especially in patients who have distal-field infarcts, ischemic ophthalmopathy, or orthostatic TIAs.…”
Section: Discussionmentioning
confidence: 92%
“…This negative reactivity may indicate a steal effect, a paradoxical response that has been observed in some patients with severe carotid artery disease. 18 The normal velocity response to hypercapnia in healthy subjects without occlusive disease (2.9-3.5%/mm Hg change in PecxV 9 -20 ) appears to be constant over the physiologic range of 20-60 mm Hg. Among patients with unilateral carotid artery occlusions, Ringelstein et al 18 have shown that vasomotor reactivity measured by TCD is severely reduced, especially in patients who have distal-field infarcts, ischemic ophthalmopathy, or orthostatic TIAs.…”
Section: Discussionmentioning
confidence: 92%
“…These effects might contribute to perfusion changes during gSW and give evidence for the significance of autonomic effects in this context, but not systematic correlation between change in heart rate and course of CBFV during gSW could be established. Cerebral perfusion is known to decrease markedly with reduction of Pco, (25). Hyperventilation-induced hypocapnia during gSW would therefore result in a major decrease in CBFV.…”
Section: Discussionmentioning
confidence: 99%
“…Enquanto é provável que poucas formas de acidente vascular cerebral relacionado à estenose carótida extracraniana ocorram por hipoperfusão 11 , na maioria dos casos, o que ocorre é embolização de uma placa aterosclerótica ou oclusão aguda da carótida e propagação do trombo distalmente 12 .…”
Section: Estenose De Carótida Extracranianaunclassified